35‐2: Proposal for Improved Calculation Method for the Halo Effect in Digital Displays Based on Human Brightness Perception. Issue 1 (28th June 2022) - Lim, Han Byul; Suh, Hyunah; Ha, Hyeyoung; Kim, Hyosun; Seo, Young-Jun; Kwon, Jaejoong; Lee, Changhee
Abstract : Evaluating the halo effects in digital displays is explained in the Information Display Measuring Standard(IDMS) as the name of halation. However, we found that the calculated halation is not well matched with the perceptual halo level, especially for those of high dynamic range(HDR) displays which show high peak luminance and low black luminance simultaneously. In addition, the values need to be moderately calibrated because the difference between displays cannot be recognized intuitively. Through subjective experiments, we found that perception of the halo effect in the display is more explainable by lightness than the luminance of the display. In this paper, we suggest a new calculation method that is more well‐matched to describe the perceptual halo effects. In the calculation, we used the lightness of the CIELAB and the maximum luminance level in the HDR.